2018
DOI: 10.1007/s12011-018-1344-8
|View full text |Cite
|
Sign up to set email alerts
|

Liver Proteome of Mice with Distinct Genetic Susceptibilities to Fluorosis Treated with Different Concentrations of F in the Drinking Water

Abstract: Appropriate doses of fluoride (F) have therapeutic action against dental caries, but higher levels can cause disturbances in soft and mineralized tissues. Interestingly, the susceptibility to the toxic effects of F is genetically determined. This study evaluated the effects of F on the liver proteome of mice susceptible (A/J) or resistant (129P3/J) to the effects of F. Weanling male A/J (n = 12) and 129P3/J (n = 12) mice were housed in pairs and assigned to two groups given low-F food and drinking water contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 64 publications
2
15
1
Order By: Relevance
“…These findings may suggest the economic and medicinal needs to find suitable herbal remedy to reduce these adverse effects of fluoride on fish. The exposure to high concentrations of fluoride could trigger the adverse toxic impact on different biological processes [8]. In different words, low concentration of fluoride (µM) might act as a promoter for cell proliferation and enzymatic activity; however, a high concentration of fluoride (mM) could act as an enzymatic inhibitor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may suggest the economic and medicinal needs to find suitable herbal remedy to reduce these adverse effects of fluoride on fish. The exposure to high concentrations of fluoride could trigger the adverse toxic impact on different biological processes [8]. In different words, low concentration of fluoride (µM) might act as a promoter for cell proliferation and enzymatic activity; however, a high concentration of fluoride (mM) could act as an enzymatic inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…Few previous studies concluded the role of fluoride as a toxic, cumulative, environmental pollutant in aquatic life [8] where they are regularly exposed to elevated concentrations of fluoride in surface waters. The adverse impact of fluoride was ensured when it enters the food chain and accumulates in different tissues of aquatic organisms, particularly fish bone and the invertebrate's exoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Small fluoride concentrations have therapeutical action against dental caries. However, exposure to high doses from water ingestion and the use of fluoride toothpastes or fluoride-rich diets increases the body burden of this ion [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…After depletion, Bradford assays [ 39 ] were performed to quantify proteins present in the pooled samples (n = 3 / group) and all samples were standardized to a concentration of 1μg/μL. Samples were submitted to proteomic analysis as previously described [ 40 ]. To 50 μL sample, 10 μL of 50 mM ammonium bicarbonate was added, before the following steps.…”
Section: Methodsmentioning
confidence: 99%